2021
DOI: 10.3390/ijerph182111015
|View full text |Cite
|
Sign up to set email alerts
|

“It Is Like We Are Living in a Different World”: Health Inequity in Communities Surrounding Industrial Mining Sites in Burkina Faso, Mozambique, and Tanzania

Abstract: Background: Health equity features prominently in the 2030 Agenda for Sustainable Development, yet there are wide disparities in health between and within countries. In settings of natural resource extraction (e.g., industrial mines), the health of surrounding communities is affected through myriad changes in the physical, social, and economic environment. How changes triggered by such projects translate into health inequities is poorly understood. Methods: This qualitative study explores potential layers of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…In addition, the existing research methods are single and the results lack accuracy. Comprehensive indicators can effectively improve the accuracy, so as to evaluate the fairness of health resource allocation more comprehensively and deeply [ 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the existing research methods are single and the results lack accuracy. Comprehensive indicators can effectively improve the accuracy, so as to evaluate the fairness of health resource allocation more comprehensively and deeply [ 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Leuenberger et al reported on a large-scale research project exploring the impact on community health of living adjacent to industrial mining sites [30]. Data was collected through 83 focus groups among communities located in Mozambique, Burkina Faso, and Tanzania.…”
Section: Tripwires and Trade-offsmentioning
confidence: 99%
“…While mining projects have been expanding in many African countries and might contribute to their economic growth, health-related studies addressing the influence of mining on the health of community subgroups, including adolescents in SSA countries remain scarce [ 21 , 22 ]. The existing literature provides evidence for their impact on local population health, migration patterns, and economic and social development [ 21 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…While mining projects have been expanding in many African countries and might contribute to their economic growth, health-related studies addressing the influence of mining on the health of community subgroups, including adolescents in SSA countries remain scarce [ 21 , 22 ]. The existing literature provides evidence for their impact on local population health, migration patterns, and economic and social development [ 21 , 23 ]. Additionally, an increasing number of studies report adverse health impacts of mining projects on different population groups in mining areas in both, the environment and its social determinants [ 21 , 23–25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation